The next generation of solution focused practice : stretching the world for new opportunities and progress - McKergow, Mark (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The Next Generation of Solution Focused Practice shows how practitioners help create change by 'stretching the world' of their clients. The book brings new ideas from enactive cognition which show how skilled attention on the client and their words is important both practically and conceptually. It provides both a summary of the development of Solution Focused Brief Therapy (SFBT) over time and how the latest developments form a newly coherent form of practice based on developing descriptions. The author has structured the book using simple and easy to understand metaphors to paint a rich, creative, and visual picture of therapy for the reader, which makes it an accessible read. This book will be of interest to a wide range of SF practitioners internationally, as well as to those involved in coaching, counselling, family therapy, education, social work, healthcare and organisational change"--
Roots of solution focused brief therapy : the interactional view -- Steve de Shazer, Insoo Kim Berg and solution focused brief therapy -- The evolution of SFBT : spreading the word and defining the practice -- Evolving the next generation of SFBT -- 'Stretching the world' of the client -- The role of the practitioner -- Introducing the solution focused art gallery -- The ticket office : permission to start/enter -- The future gallery : miracles, parallel worlds and more -- The past gallery : instances connected to the better future -- The gift shop : what to take away? -- Revisiting the gallery : follow-on sessions -- A solution focused aesthetic : what is beautiful and why.
OCLC-licensed vendor bibliographic record.
Keywords: Solution-focused brief therapy; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health